1987
DOI: 10.1002/nme.1620241013
|View full text |Cite
|
Sign up to set email alerts
|

Field‐consistency and violent stress oscillations in the finite element method

Abstract: SUMMARYThe fact that finite element models can give rise to violent stress oscillations and that there are optimal locations whcrc strcsscs can bc correctly sampled in spite of the presence of these violent stress Iluctuations has been known for some time. Howcvcr, it is less wcll known that these oscillations arise in a specific class of problems--where there arc multiplc strainfields arising from one or more field-variables and where one or more of these strain-fields must be constrained in particular physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…This study, in general, suggests that for the plate thickness parameter a=h of the order 10, the original spline element does not seem to su er from locking problems whereas it is susceptible to shear locking for the fairly thin as well as extreme thin cases. Furthermore, one can conclude that unlike element employing the reduced integration scheme, which may not be suitable for the problems wherein a higher order of integration is needed (for instance tapered plates), consistent element frees the order of integration and thus, is applicable for both thick and extreme thin situations, as expected [19][20][21]. Finally, it can be viewed that the consistency approach with constant level (CS-3) alone yields accurate results for fairly thick to extremely thin plates.…”
Section: Numerical Experimentsmentioning
confidence: 87%
See 2 more Smart Citations
“…This study, in general, suggests that for the plate thickness parameter a=h of the order 10, the original spline element does not seem to su er from locking problems whereas it is susceptible to shear locking for the fairly thin as well as extreme thin cases. Furthermore, one can conclude that unlike element employing the reduced integration scheme, which may not be suitable for the problems wherein a higher order of integration is needed (for instance tapered plates), consistent element frees the order of integration and thus, is applicable for both thick and extreme thin situations, as expected [19][20][21]. Finally, it can be viewed that the consistency approach with constant level (CS-3) alone yields accurate results for fairly thick to extremely thin plates.…”
Section: Numerical Experimentsmentioning
confidence: 87%
“…At the simplest level of ÿeld-consistency, we consider the use of ÿeld redistributed substitute interpolation functions which include only those speciÿc terms that must be made ÿeld-consistent, as outlined in References [19][20][21]. This is achieved here by smoothing the original interpolation function in a least-squares accurate fashion to the desired form i.e.…”
Section: Q-element-the Element Based On Level 1 Consistency (Cs-1)mentioning
confidence: 99%
See 1 more Smart Citation
“…This study, in general, suggests that for the beam thickness parameter¸/t of the order 100, the original spline element does not seem to su!er much from locking problems whereas it is susceptible to membrane and shear locking for the extreme thin case. Furthermore, one can conclude that unlike elements employing the reduced integration scheme, which may not be suitable for the problems wherein a higher order of integration is needed (for instance tapered beams), consistent element frees the order of integration and thus, is applicable for both thick and extreme thin situations, as expected [22,23]. Finally, it can be opined that the consistency approach with constant level (CMCS-3) alone produces good results for fairly thick to extremely thin beams.…”
Section: Numerical Experimentsmentioning
confidence: 88%
“…Carpenter et al [4] credited the coupling between bending and shear rotation in the Timoshenko beam equations as causing shear locking and suggested that these be decoupled through the use of appropriate strain fields. Using the concept of field consistency, Prathap [5,6] attributed shear locking to the choice of interpolation functions used for displacement fields, which impose spurious constraints that occur because the strains developed from the displacement approximation are inconsistent. Discussions of different interpolation schemes for the transverse displacement and sectional rotation which determine various Timoshenko beam finite element models have been given by Reddy [7].…”
Section: Introductionmentioning
confidence: 99%